2012
DOI: 10.1523/jneurosci.2384-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Tune It Down to Live It Up? Rapid, Nongenomic Effects of Cortisol on the Human Brain

Abstract: The stress hormone cortisol acts on the brain, supporting adaptation and time-adjusted coping processes. Whereas previous research has focused on slow emerging, genomic effects of cortisol, we addressed the rapid, nongenomic cortisol effects on in vivo neuronal activity in humans. Three independent placebo-controlled studies in healthy men were conducted. We observed changes in CNS activity within 15 min after intravenous administration of a physiological dose of 4 mg of cortisol (hydrocortisone). Two of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Cortisol induces rapid changes in neuronal information processing [30] by acting on receptors at the neuronal membrane [31]. It has been shown previously that increases in dual-task performance similar to those observed in the current study are evident when punishments are provided in case of slow reaction times [22].…”
Section: Discussionsupporting
confidence: 86%
“…Cortisol induces rapid changes in neuronal information processing [30] by acting on receptors at the neuronal membrane [31]. It has been shown previously that increases in dual-task performance similar to those observed in the current study are evident when punishments are provided in case of slow reaction times [22].…”
Section: Discussionsupporting
confidence: 86%
“…any effect occurring within 10 min precludes the time required for translocation, transcription and translation [34]. One recent study combining experimental cortisol infusion and neuroimaging techniques has confirmed that cortisol exerts rapid effects on neuronal activity; however, this technique does not yet provide an actual functional index of feedback signalling [30]. This study will provide the proof of concept for a systems-based index of rapid cortisol inhibitory feedback signalling.…”
Section: Introductionmentioning
confidence: 84%
“…These data suggest that this mathematical model may provide a unique window into the central nervous system mechanisms underlying HPA feedback control. Future studies might investigate this possibility by looking at the correlation between this model parameter and other purported measures of feedback signalling, such as the DST or neuroimaging during cortisol injections [30]. However, the results of DST may differ from feedback regulation by endogenous cortisol owing to differences in potency, receptor binding affinity, specificity of rapid glucocorticoid receptor mechanisms, access to brain receptors and time scales of the underlying neural mechanisms [24,31,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of previous reports on the effects of exogenous cortisol on blood perfusion in the thalamus (86), it was hypothesized that cortisol may act as a filter in the integration of exteroceptive and interoceptive sensory information (19). Biologically active cortisol is converted into inactive cortisone by the enzyme 11β-hydroxysteroid dehydrogenase type 2 (56).…”
Section: Discussionmentioning
confidence: 99%